2022
DOI: 10.3389/fphar.2022.1023533
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of oncolytic virus combined with chemotherapy or immune checkpoint inhibitors in solid tumor patients: A meta-analysis

Abstract: Background: In recent years, several clinical trials have focused on oncolytic virus (OVs) combined with chemotherapy or immune checkpoint inhibitors (ICIs) in solid tumor patients, which showed encouraging effects. However, few studies have concentrated on the summary on the safety and efficacy of the combined treatments. Therefore, we conducted this meta-analysis to explore the safety and curative effect of the combined therapy.Methods: We searched the PubMed, Cochrane Library, Embase, and Clinicaltrials.gov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“… 205 So chemotherapy certainly remains an important partner in combination with OV therapy too, although more clinical data are needed to substantiate this. 206 Another important aspect of combinational ICI with chemotherapy or OV therapies in clinical trials so far is the occurrence of patients undergoing complete tumor regression (so-called "elite responders"). Although these elite responders are often only a small fraction of the total amount of patients in each clinical trial, they are nevertheless very valuable and can offer us a way to get important new insights into how immunotherapeutic responses can be improved.…”
Section: Introductionmentioning
confidence: 99%
“… 205 So chemotherapy certainly remains an important partner in combination with OV therapy too, although more clinical data are needed to substantiate this. 206 Another important aspect of combinational ICI with chemotherapy or OV therapies in clinical trials so far is the occurrence of patients undergoing complete tumor regression (so-called "elite responders"). Although these elite responders are often only a small fraction of the total amount of patients in each clinical trial, they are nevertheless very valuable and can offer us a way to get important new insights into how immunotherapeutic responses can be improved.…”
Section: Introductionmentioning
confidence: 99%
“…OVs stimulate anti-tumor immune responses, and ICIs function to remove inhibitory signals on effector immune cells. Therefore, it is possible that hematological toxicities, such as neutropenia, anemia, and thrombocytopenia, may occur with combined therapy [ 26 , 27 ]. Furthermore, innate and adaptive immune responses against the virus itself limits the potential of OVs [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several meta-analyses have already confirmed that combining oncolytic viruses with chemotherapy is effective and safe for patients with tumors ( Li Z. et al, 2020 ; Li et al, 2020 Y. ; Liu et al, 2022 ). Nonetheless, there are still debates on whether patients with advanced solid tumors can benefit from the treatment of pelareorep combined with palliative chemotherapy.…”
Section: Discussionmentioning
confidence: 99%